Analisis Model Kepemimpinan dalam Manajemen Pendidikan Islam (Studi Kasus di SDN Sukaharja II) - Supriadi, Agus; Hakim, Lukmanul (Penerbit Minhaj Pustaka, 2024)
Islamic educational leadership will always incorporate Islamic values in its leadership. Communication between superiors and subordinates is not only in the organizational realm, but in Islam there is fostering of relationships between human beings. Leadership education is expected to be able to make corrections to existing behavior in the organization, and the leadership of an institution is able to implement quality standards. A leader is required to master various matters related to improving the quality of education. Therefore, with competition so tight in the world of education, Islamic education must have new, innovative breakthroughs so that it is not inferior to educational institutions in general. Leadership in relation to the quality of Islamic education is a very important element in an educational institution, because leadership, in this case the leader must be able to become a managerial person who can guide and direct and be able to generate motivation in the institution he leads in improving the performance of those he leads, so that the vision and mission and the goals of an educational institution will be achieved. Quality improvement and management development are given great attention. Individuals as leaders are responsible for Islamic educational institutions. Leadership development can be interpreted as expanding a person's capacity to carry out management to achieve something more effective in leadership roles and processes. Abstrak Kepemimpinan pendidikan Islam akan selalu menjadikan nilai-nilai Islam dalam kepemimpinannya. Komunikasi antara atasan dan bawahan tidak hanya dalam ranah organisasi saja, namun dalam Islam terdapat pembinaan hubungan antar sesama manusia. Pendidikan kepemimpinan diharapkan mampu melakukan koreksi terhadap perilaku yang ada dalam organisasi, dan pimpinan suatu lembaga mampu menerapkan standar mutu. Seorang pemimpin dituntut menguasai berbagai hal yang berhubungan dalam rangka peningkatan mutu pendidikan. oleh karena itu, dengan persaingan yang begitu ketat dalam dunia pendidikan, maka pendidikan Islam harus mempunyai terobosan-terobosan baru yang bersifat inovatif sehingga tidak kalah dengan lembaga pendidikan pada umumnya. Kepemimpinan dalam kaitannya dengan mutu pendidikan Islam merupakan elemen yang sangat penting dalam suatu lembaga pendidikan, karena kepemimpinan dalam hal ini pemimpin harus mampu menjadi seorang menejerial yang dapat membimbing dan mengarahkan serta mampu membangkitkan motivasi dilembaga yang dipimpinnya dalam meningkatkan kinerja yang dipimpinnya, sehingga visi misi dan tujuan sebuah lembaga pendidikan akan tercapai.Peningkatan kualitas dan pengembangan manajemen sangat diperhatikan. Individu sebagai pemimpin keberadaannya bertanggung jawab terhadap lembaga pendidikan Islam, pengembangan kepemimpinan (leadership development) keberadaannya dapat diartikan sebagai perluasan kapasitas seseorang dalam menjalankan suatu manajemen untuk mencapai sesuatu yang lebih efektif dalam peran dan proses kepemimpinan.